2006
DOI: 10.2118/94081-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Predicting Liquid Loading in Gas Wells

Abstract: Loading up of liquids in wellbore has been recognized as one of the severe problems in gas production for many years. Accurate prediction of the problem is vitally important for taking timely measures to solve the problem. Although previous investigators have suggested several methods to predict the problem, results from these methods often show discrepancies. Also, these methods are not easy to use because of the difficulties with prediction of bottomhole pressure in multiphase flow. An accurate and easy-tous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 5 publications
0
29
0
1
Order By: Relevance
“…It has been observed by Turner et al 3 11 that the flow stream velocity required to continuously move the liquid film along the conduit wall is consistently greater than that required to suspend and lift the entrained liquid droplets upward in the flow stream. As noted by Turner et al 3 , as well as from field observations of wellbore liquid unloading conditions [4][5][6][7][8][9][10][11] , that the criteria for the translation of entrained liquid droplets in the flow stream generally provides a better indication of the ability of a well to continuously transport wellbore liquids to the surface.…”
Section: Introductionmentioning
confidence: 94%
“…It has been observed by Turner et al 3 11 that the flow stream velocity required to continuously move the liquid film along the conduit wall is consistently greater than that required to suspend and lift the entrained liquid droplets upward in the flow stream. As noted by Turner et al 3 , as well as from field observations of wellbore liquid unloading conditions [4][5][6][7][8][9][10][11] , that the criteria for the translation of entrained liquid droplets in the flow stream generally provides a better indication of the ability of a well to continuously transport wellbore liquids to the surface.…”
Section: Introductionmentioning
confidence: 94%
“…As presented in Table 1, several investigators have suggested different modified expressions derived from Turner model. Turner et al, 1969 Created the widely accepted Turner equation Coleman et al, 1991 Suggested not to use the 20% correction factor for low pressure gas wells Nosseir et al, 2000 Considered influences from different flow regimes Li et al, 2002 Involved the droplets' shape Veeken et al, 2003 Defined the concept of Turner ratio Guo et al, 2006 Took the minimum required kinetic energy of gas flow into account Belfroid et al, 2008 Concerned with the effects due to wellbore inclination Sutton et al, 2010 Used more realistic PVT properties Zhou and Yuan, 2010 Included the liquid droplet concentration in gas wells Veeken et al, 2010 Designed a specific expression for offshore gas wells Luan and He, 2012 Comprised droplets rollover in the gas rising process…”
Section: Current Prediction Approachesmentioning
confidence: 99%
“…It is possible that interfacial shear stress calculated with the Wallis (1969) correlation is too small at the transition from annular to intermittent flow. Many other interfacial-friction-factor correlations have been developed to match the experimental data, such as Fore et al (2000), Andritsos and Hanratty (1987), Whalley and Hewitt (1978), and Henstock and Hanratty (1976). Among these correlations, the correlation of Fore et al (2000) exhibited the best match with field data.…”
Section: New Model For Predicting Liquid Loadingmentioning
confidence: 99%